Randomized Controlled Trial Quality in Pediatric Physical Therapy. (1st August 2014) - Paci, Matteo; Landi, Niccolò; Marchettini, Mariangela; Baccini, Marco
ABSTRACT The aim of this study is to describe the reported quality of randomized controlled trials (RCTs) in pediatric physical therapy (PPT) and changes with time. All RCTs sourced from PEDro database and scored using the PEDro scale were included. RCTs were classified as high- or low quality both with the original cut-off of 6 and a modified cut-off of 5. The relationship between PEDro scores and year of publication was also investigated. One thousand three hundred sixty-seven articles were analyzed. According to the PEDro scale original and modified cut-off, 29% and 56% of the articles were classified as high-quality studies, respectively. The number of RCTs and the average PEDro score increased between 1962 and 2012. However, since some items of the scale could be more frequently satisfied, a further improvement of the quality of RCTs in PPT is recommended.